2006
DOI: 10.1002/cncr.22200
|View full text |Cite
|
Sign up to set email alerts
|

Health profiles of younger and older breast cancer survivors

Abstract: BACKGROUND.Over the past several decades, the incidence of prolonged survival after a diagnosis of cancer has increased; however, little is known regarding the long‐term health profiles of cancer survivors in general and of breast cancer survivors in particular. To obtain more information concerning the consequences of surviving breast cancer, the authors conducted a large‐scale health survey of patients who had been treated for the disease at their institution.METHODS.A descriptive analysis of information was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…Analysis of these data has allowed us to report on the long-term effects of cancer such as hearing loss [14], diabetes [13] and cataracts [15], and the influence of ethnicity [11] on survivorship. We have also been able to study survivorship in specific groups, such as survivors of thyroid cancer [12], melanoma [16], and breast cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these data has allowed us to report on the long-term effects of cancer such as hearing loss [14], diabetes [13] and cataracts [15], and the influence of ethnicity [11] on survivorship. We have also been able to study survivorship in specific groups, such as survivors of thyroid cancer [12], melanoma [16], and breast cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…185 Psychological distress is significantly greater among AYAs compared with older adults. [194][195][196][197][198] In a longitudinal study that assessed the prevalence of psychological distress in 215 AYA patients with cancer (15-39 years of age) during the first year after diagnosis, distress symptoms exceeded population norms at the time of diagnosis and at 12-month follow-up. 195 In this study, 12% of AYA patients reported clinically significant chronic distress throughout the first 12 months after diagnosis and an additional 15% reported delayed distress.…”
mentioning
confidence: 99%
“…84 Recent studies suggest that the rates of psychological distress are significantly greater among AYAs compared with older adults. [89][90][91] Kazak et al 92 recently reported that intensive cancer treatments during adolescence are associated with inferior psychosocial outcomes and health beliefs in survivors compared with their age-matched peers. Psychological problems are also associated with an increased risk for obesity and poor heath behavior, which may increase future risk for chronic health conditions and secondary neoplasms.…”
mentioning
confidence: 99%